REPOSISI DISTRIK DI PAPUA ; Perspektif Kebijakan Penataan Kewenangan - Muliadi Anangkota (Universitas Cenderawasih, 2018)
This article is the result of an assessment of the problematic developments in Papua District implemented. authors focus on the changes to the District Sub as mandated special autonomy law. In fact to date has not been set by regulation District Autonomy, consequently regencies / cities in Papua still use a set of national regulations in the District. so that changes in the District of Papua is not in accordance with the mandate of the Special Autonomy Law. So that District in Papua is still the same as before the District enacted the Special Autonomy Law. The discussion in this article examines the arrangement of the authorities of the district, with the concept of authority district in Papua should be in accordance with the geographic characteristics, population and territory of Papua. structuring of authority district in Papua can be done with a partial withdrawal of delegation and authority of the regents / mayor.